Murine transfer of a human gene variant associated with exceptional longevity displays senolytic effects both in immune compartment and endothelium of aged mice. (25th November 2020) - Ciaglia, E; Montella, F; Malavolta, M; Carrizzo, A; Lopardo, V; Vecchione, C; Puca, A.A
Abstract: : The persistence and accumulation of senescent cells has been shown to potentially play a role in the pathophysiology of age-related cardiovascular diseases. Indeed with time, a decline in immune efficacy, termed immunesenescence, and a deleterious secretory phenotype of senescent cells (SASP) generate that inflammatory background mainly mediating the elderly cardiovascular phenotype. Long Living Individuals (LLI) which delay aging, represent a model of positive biology and an exceptional resource to study and find a way to improve general public health. Previous studies from our group have shown that a human gene associated with exceptional longevity (LAV-BPIFB4) was able to block the atherosclerotic process in ApoE−/− mice by conferring the animals with a pro-resolving M2 macrophages profile. Furthermore, LAV-BPIFB4 promotes the recruitment of hematopoietic stem cells, reparative vascularization and frailty reduction. Here we sought to underpinn the role of LAV-BPIFB4 in counteracting the age-related remodeling of the immune responses. The effects of systemic adeno-associated viral vector-mediated LAV-BPIFB4 gene transfer on the immune dynamics in old mice have been investigated by an extensive flow cytometric approach in lymphoid tissues (bone marrow, spleen and peripheral blood). C57BL/6J mice were assigned to two age-matched experimental groups: a treatment group (AAV-LAV-BPIFB4; N=6 mice, aged 18–23 months and a control group (AAV-GFP; N=6 mice, aged 18–23 months. 30th and 60th day since the beginning of the infection, SA-beta Gal substrate has been used to identify CD45+ senescent cells in freshly isolated PBMC, splenocytes, bone marrow (BM)-derived cells. As expected, we monitored an increase in SA-betaGal activity in blood. This increase is most significant in CD11b+ myeloid cells, whithout affecting neither CD3+T neither NK1.1+Natural Killer (NK) cell compartment. Notably 30 days AAV-LAV-BPIFB4 infection and to a more the 60 days-treatment, resulted in a significant decrease in senescent pool of peripheral immune cells and a concomitant enrichment of senescent cells in spleen. Concomitantly, aorta from AAV-LAV treated mice showed significant reduction in SA-beta Gal positive area. Furthermore a LAV-BPIFB4 induction of pro-resolving M2 macrophages compared to control group was documented in the main haemocateretic organ. As consequence the senolytic effect of LAV-BPIFB4 gene-therapy well correlated with the rescue of proliferative index of splenocytes upon PHA stimulation, and their functional protective response to lipopolysaccharide (LPS) in term of IL-6 and TNF-alpha secretion. The restoration of a protective and balanced immune response finally reflected the reduction of senescent phenopype acquired by mouse aortic endothelial cells during the aging process in vivo. A better underpinning of the senolytic action of LAV-BPIFB4 may offer a valuable therapeutic tool to reverse aging phenotype causing most of cardiac diseases Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Cariplo Foundation (n.2016-0874) to AAP and CV